2023
DOI: 10.1002/adma.202301468
|View full text |Cite
|
Sign up to set email alerts
|

High‐Contrast Bidirectional Optoelectronic Synapses based on 2D Molecular Crystal Heterojunctions for Motion Detection

Abstract: Light‐stimulated optoelectronic synaptic devices are fundamental compositions of the neuromorphic vision system. However, there are still huge challenges to achieving both bidirectional synaptic behaviors under light stimuli and high performance. Herein, a bilayer 2D molecular crystal (2DMC) p‐n heterojunction is developed to achieve high‐performance bidirectional synaptic behaviors. The 2DMC heterojunction‐based field effect transistor (FET) devices exhibit typical ambipolar properties and remarkable responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 70 publications
0
18
0
1
Order By: Relevance
“…The training process is a gradual learning process and it can also be presented by confusing the colors of the diagonals in the matrix. 48 When the maximum inferred output value of each row gradually agrees with the desired output value of each column, it indicates that successful recognition of the digits is achieved. As shown in Figure S9a-i, Supporting Information, the recognition accuracy increases as the number of training epoch increases.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The training process is a gradual learning process and it can also be presented by confusing the colors of the diagonals in the matrix. 48 When the maximum inferred output value of each row gradually agrees with the desired output value of each column, it indicates that successful recognition of the digits is achieved. As shown in Figure S9a-i, Supporting Information, the recognition accuracy increases as the number of training epoch increases.…”
mentioning
confidence: 89%
“…As shown in Figure h, it can be found that the recognition rate under DUV light stimulation is the largest at 94% after 20 training epochs. The training process is a gradual learning process and it can also be presented by confusing the colors of the diagonals in the matrix . When the maximum inferred output value of each row gradually agrees with the desired output value of each column, it indicates that successful recognition of the digits is achieved.…”
mentioning
confidence: 99%
“…In this study, a series of poly The perception of visual information by an organism is a complex physiological process involving various neurons and synapses (Figure 1a). 18,19 Biological vision was simulated by the artificial photoelectric synapses. Semiconducting block copolymers with novel helical structures were prepared thanks to the inspiration of functional helical structures in nature (Figure 1b), and for the first time, the helical nanowires were utilized as the active layer of synaptic devices (Figure 1c).…”
mentioning
confidence: 99%
“…43−47 Moreover, the mechanical integrity of the ambipolar devices can also be enhanced via mixed-dimensional nanoparticle−nanowire p-n channels and bidirectional plasticity of the ambipolar devices has potential uses in reversible information processing and neuromorphic algorithms. 48 Here, an ion-impermeable zero-dimensional inorganic film and ion-permeable one-dimensional organic film were employed as n-type 49,50 and p-type 51−53 integrity and asymmetric bidirectional synaptic plasticity. Being a crucial component of the analogous somatosensory nerves, the device can be exploited to achieve the perception of visible light, signal processing, and behavior driving.…”
mentioning
confidence: 99%
“…The electrolyte-type transistor benefits from a high carrier concentration and a low operating frequency due to the unique ion–electronic interface interaction, which enables switching and gain functionalities in the component. For example, some reports have demonstrated the great potential of the dual-carrier (holes and electrons) strategy for regulating plasticity in the synaptic transistor by utilizing the distinct ion interfacial behaviors on organic and inorganic films, respectively. Limited by the rare p - type oxide semiconductor (oxygen vacancies can also annihilate holes) and poor n - type organic semiconductor (species can also interact or react with the injected electrons), with this carrier complementary strategy, the combination of the channels for inorganic n - type and organic p - type films may be the optimum lineup to acquire the relatively stable bidirectional synaptic plasticity. Moreover, the mechanical integrity of the ambipolar devices can also be enhanced via mixed-dimensional nanoparticle–nanowire p-n channels and bidirectional plasticity of the ambipolar devices has potential uses in reversible information processing and neuromorphic algorithms …”
mentioning
confidence: 99%